Tindak Pidana Penyuapan oleh Korporasi dari Sudut Pandang Teori Identifikasi - Lie, Hendrik; Putri, Fadiyah Ramadhani; Tanlilessy, Inggrid Florencya (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2020)
Corporations can become legal subjects of criminal acts of corruption and be criminalized under the Law on the Eradication of Corruption in Indonesia. One of the theories that can be used to make corporations as perpetrators of criminal acts of corruption is the identification theory. It sees the actus reus and mens rea of ??the management as a reflection of the actus reus and mens rea of ??the corporation itself so that the actions of the management must be considered the actions of the corporation. As a result, it is interesting to analyze whether a corporation can be held responsible for the bribery crime committed by corporate management to benefit the corporation from the identification theory? This research is a normative juridical study using a statutory approach and a conceptual approach, to conclude that a corporation can be convicted if the corporation has fulfilled the elements of the criminal act of bribery, and has actus reus and mens rea in committing the act. Based on these results, the Corruption Eradication Commission should emphasize the form of criminal responsibility by corporations and managers for corporate actions and management in carrying out corruption cases committed in the interest of the corporation.